Analisis Tingkat Kerawanan Longsor Dengan Integrasi Analytical Hierarchy Process dan Pemodelan Spasial Sistem Informasi Geografis di Kabupaten Aceh Tenggara - Juni Muchlis Mustafa; Sirojuzilam Sirojuzilam; Nurdin Sulistiyono (Jurnal Serambi Engineering, 2019)
Southeast Aceh District in Aceh Province is a district that often experiences landslides. High rainfall (1600 mm/year) and hilly areas with slope levels above 40% are also indicators of landslide vulnerability. The study aims to determine the criteria for the biggest contributors to landslide vulnerability using the Analytical Hierarchy Process (AHP) method and find out the distribution of landslide vulnerability in Southeast Aceh District by using spatial modeling using Geographic Information Systems (GIS). Spatial data as a parameter in making landslide models includes 4 (four) parameters, they are land cover, rainfall, slope and soil movement.  These parameters have sub-parameters such as land cover parameters that have sub-parameters, i.e empty land,  shrubs, rice fields, fields/moor, gardens, settlements, rivers, secondary forests and primary forests. The slope parameters have sub-parameters i.e slope 0-8%, slope of 8-15%, slope of 15-25%, slope of 25-45%, slope 45%. Rainfall parameters have sub-parameters which are 2,500-2,700 mm/yr, 2,700-2,900 mm/yr, 2,900-3,400 mm/ yr, 3,400-3,600 mm/yr and 3,600-3800 mm/yr. The parameters of soil motion have sub-parameters, i.e middle and middle high movements. These parameters and sub-parameters become questionnaires by Expert Choice 11 as Analytical Hierarchy Process (AHP) software. This questionnaire then becomes an interview material for expert experts to determine the weight values (parameters) and scores (sub-parameters). The weight values and scores obtained from the Expert Choice 11 application are used by the ArcGIS 10.6 to create a spatial model of the distribution of landslide vulnerabilities. Research has produced spatial distribution of landslide vulnerability with a low level of vulnerability distribution of 209,523.56 ha (49%), moderate vulnerability of 158,170.14 ha (37%) and high vulnerability of 56,640.76 (13%)